Analyzing the Role of Classroom Management in Enhancing Fifth-Grade Elementary Students’ Learning Outcomes - Agustina, Agnes; Wilade, Surahman; Rizal, Rizal; Pahriadi, Pahriadi (Journal of Innovation and Research in Primary Education, 2025)
Classroom management constitutes a fundamental component of effective elementary education, yet its specific role in enhancing student learning outcomes remains insufficiently investigated, particularly at the fifth-grade level where academic demands intensify. This qualitative case study examined the role of classroom management in improving fifth-grade students' learning outcomes at Ongulero Public Elementary School during the 2024/2025 academic year. Data were collected through classroom observations, semi-structured interviews with two teachers and twenty students, questionnaires, and documentary analysis, focusing on five dimensions: physical environment organization, discipline enforcement, behavior guidance, teacher-student communication, and classroom organization. Findings revealed that teachers demonstrated exemplary performance in discipline enforcement and teacher-student communication (100% excellent ratings), strong performance in behavior guidance (90% excellent), while physical environment organization (60% excellent) and classroom organization (50% excellent) showed moderate effectiveness requiring further development. The study provides empirical evidence that effective classroom management functions as a multidimensional construct encompassing relationship-building, spatial design, behavioral regulation, and collaborative governance systems. These findings suggest that professional development should adopt differentiated approaches, building upon existing strengths in discipline and communication while enhancing organizational dimensions. The successful integration of culturally grounded practices within universal management frameworks offers valuable insights for educators in collectivist cultural contexts, contributing to both theoretical understanding and practical implementation of classroom management in elementary education.